ปัจจัยแห่งความสำเร็จของระบบเรียกเก็บเงินชดเชย ค่ารักษาพยาบาล ผู้ป่วยโครงการหลักประกันสุขภาพ ถ้วนหน้าของโรงพยาบาลมหาราชนครเชียงใหม่ - เพลินพิศ วงศ์สุวรรณ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2017)
The independent study titled “Success Factors of the Claims System for Patients Under the Universal Coverage Scheme at Maharaj Nakorn Chiang Mai Hospital” was performed with the following objectives: to determine success factors for implementing an information technology IT system to collect compensation for patient medical expenses under the Universal Coverage Scheme, and to propose a method for implementing an IT system to improve the claims system of the Maharaj Nakorn Chiang Mai Hospital. Quantitative data were collected from 200 personnel involved in the claims system to collect compensation for patient medical expenses under the Universal Coverage Scheme at Maharaj Nakorn Chiang Mai Hospital. A sample size of 133 cases was obtained using a Yamane’s formula. Random sampling was done from a population among various divisions in the hospital involved in the claims system. Data were analyzed using the Statistical Package for Public Administration Research to obtain descriptive statistics including frequency, percentage, mean and standard deviation. The inferential statistics used to test the hypothesis employed multiple regression. The significance level of statistical testing was set at 0.05 for determining the quality of services from data obtained by questionnaire. The results demonstrated that two important factors that determined the success of implementing an IT system for collecting patient medical expenses under the Universal Coverage Scheme at the Maharaj Nakorn Chiang Mai Hospital: an organization’s structure and its workforce. A favorable organizational structure included an agile administration structure, clear division of responsibility and job allocation based on personnel expertise. A collaborative network among different divisions and a clear chain of command also reduced work process redundancy leading to a successful organizational administration and an increased management efficiency and work flexibility. An organization’s workforce is another important factor for a successful claims system. The hospital personnel’s confidence and dedication to accomplish assignments, as well as their knowledge, competency and ability to work as a team, were all part of the workforce factor. Results from this study lead to the following recommendations: 1) A workforce should be recruited and placed based on the requirements of a particular work position. 2) An organization should assess staffing levels required for work processes of IT system to prevent a negative impact on work efficiency. 3) Workforce training should be part of an organization’s annual action plan to provide the necessary skills and competencies required for workforce to perform work processes in the IT system. 4) A decentralized organization structure is preferable to reduce redundancy of work processes and administrative steps, resulting in an agile and streamlined work system.